An Alternative Route to Voting Reform: the Right to Vote, Voter Registration, Redistricting and U.S. State Constitutions. Issue 3 (13th June 2019) - Martorano Miller, Nancy; Hamm, Keith E; Aroca, Maria; Hedlund, Ronald D
Abstract: The U.S. Constitution reserves to states the responsibility for regulating most aspects of elections. Recently, the Supreme Court has weakened the tools for federal officials to challenge state elections practices under the Voting Rights Act and signaled a great deal of deference to state authority over election law. As a result, state legislatures' latitude to regulate elections is constrained primarily by state constitutions. With voter ID laws and partisan gerrymandering commanding considerable attention in recent years, it is important to investigate the importance of state constitutions in this area. In this article, we discuss recent efforts by voting and election reformers to utilize state constitutions to challenge restrictive voting laws and partisan gerrymandering, whether by enacting state constitutional amendments or relying on state constitutional provisions in state court litigation. We also highlight the diverse and often underappreciated landscape of voting and election laws in the states and the resources available to reformers at the state level by analyzing state constitutional provisions bearing on the right to vote, voter registration, and redistricting.